An Ethnobotanical Study of Tongkat Ali (Eurycoma longifolia Jack) on Malay Ethnic Group in Tanjung Balai, Karimun, Riau Islands - Wardah Wardah; Marwan Setiawan (The Ethnobiological Society of Indonesia, 2021)
Tongkat ali (Eurycoma longifolia Jack) is one of the tropical forest plants in Indonesia, which is utilized as a raw material in the manufacture of various modern and traditional medicines. However, information regarding the potential and conservation of this plant in indigenous communities in Karimun, Riau Islands has not been well-documented. Therefore, researchers conducted a study in Pongkar Village and Karimun Anak, Tabing, Riau Islands concerning the potential and conservation of tongkat ali for the lives of the people in these research locations. Data were collected through an ethnobotanical approach and interviews with selected respondents, traditional healers, village heads, the representative from Karimun Forestry Conservation Office, and local people who utilize this plant in their daily lives. The results showed that the local community utilized tongkat ali (Eurycoma longifolia Jack) as medicinal ingredients to treat fever caused by malaria, to increase stamina, and to be an alternative source to increase the family’s income. In addition, efforts to conduct in-situ and ex-situ conservation supported by the community, indigenous communities, and government agencies are highly needed so that its utilization can be carried out sustainably.